NLRP3 inflammasome in Alzheimer’s disease: molecular mechanisms and emerging therapies - Li, Zhitao; Gong, Chunrong (Frontiers in Immunology, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline, memory impairment, and neuroinflammation, with no definitive cure currently available. The NLRP3 inflammasome, a key mediator of neuroinflammation, has emerged as a critical player in AD pathogenesis, contributing to the accumulation of β-amyloid (Aβ) plaques, tau hyperphosphorylation, and neuronal damage. This review explores the mechanisms by which the NLRP3 inflammasome is activated in AD, including its interactions with Aβ, tau, reactive oxygen species (ROS), and pyroptosis. Additionally, it highlights the role of the ubiquitin system, ion channels, autophagy, and gut microbiota in regulating NLRP3 activation. Therapeutic strategies targeting the NLRP3 inflammasome, such as IL-1β inhibitors, natural compounds, and novel small molecules, are discussed as promising approaches to mitigate neuroinflammation and slow AD progression. This review underscores the potential of NLRP3 inflammasome inhibition as a therapeutic avenue for AD.